Legal Aspects Of Non-Performing Loan Settlement At BANK BRI In Boalemo - Fibriyanti Lakoro; Ikbal Kadir (CV. Akira Java Bulu, 2025)
This study aims to analyze the implementation of cessie as a legal mechanism in resolving non-performing loans at Bank BRI Boalemo, focusing on its collaboration with the Tilamuta District Attorney's Office. Using a normative legal research method combined with empirical field data, the study examines statutory regulations such as the Indonesian Civil Code, Banking Law, Fiduciary Guarantee Law, and OJK regulations. Data were collected through literature review and interviews with relevant stakeholders. The results show that cessie provides an effective non-litigation solution in the transfer of receivables from banks to third parties, allowing for faster credit recovery and reduced litigation costs. From 2022–2024, 12 cases of non-performing loans were addressed through cessie, with 8 successfully recovered. However, challenges remain, including limited understanding of cessie by debtors, difficulty in finding third-party buyers, and lack of technical regulatory guidance. The study concludes that cessie, supported by inter-institutional cooperation, particularly with the prosecutor’s office, is a strategic tool for efficient, lawful debt recovery while preserving legal certainty and fairness for both creditors and debtors.